Selubung Ketidakadilan Peran Gender dalam Motherhood pada Film Athirah - Siautta, Sarah Yoshina; Widyaningrum, Anastasia Yuni; Setyarinata, Agatha Winda (Universitas Brawijaya, 2020)
Often times Indonesian films raise issues around women, especially about mothers, which is linked to gender inequality between men and women. The films that depict women unfairly in a disadvantageous position is a product of patriarchal culture. Women, especially mothers, often have less dominant roles and positions in all fields; also women are rarely used as main characters. The same is the case with the characterization of the mother in the film Athirah. In this study, we discussed about how motherhood is shown in the film Athirah. This study employed semiotic method proposed by Charles Sander Peirce. The results of this study indicate that Athirah's motherhood revolves around her role as a wife and husband's companion, as a household organizer and leader, and also as a child caregiver. The depiction of motherhood in the film Athirah is still trapped in the classic depiction of a woman in an unequal gender construction. This inequality is shown in the double burden carried by Athirah's figure.